Effects of soft X‐ray radiation damage on paraffin‐embedded rat tissues supported on ultralene: a chemical perspective. (6th April 2018) - Bedolla, Diana E.; Mantuano, Andrea; Pickler, Arissa; Mota, Carla Lemos; Braz, Delson; Salata, Camila; Almeida, Carlos Eduardo; Birarda, Giovanni; Vaccari, Lisa; Barroso, Regina Cély; Gianoncelli, Alessandra
Abstract : The radiation damage on biological tissues as a result of soft X‐rays is assessed, focusing on the effects upon the embedding and supporting media that can influence further analyses. Abstract : Radiation damage is an important aspect to be considered when analysing biological samples with X‐ray techniques as it can induce chemical and structural changes in the specimens. This work aims to provide new insights into the soft X‐ray induced radiation damage of the complete sample, including not only the biological tissue itself but also the substrate and embedding medium, and the tissue fixation procedure. Sample preparation and handling involves an unavoidable interaction with the sample matrix and could play an important role in the radiation‐damage mechanism. To understand the influence of sample preparation and handling on radiation damage, the effects of soft X‐ray exposure at different doses on ultralene, paraffin and on paraffin‐embedded rat tissues were studied using Fourier‐transform infrared (FTIR) microspectroscopy and X‐ray microscopy. Tissues were preserved with three different commonly used fixatives: formalin, glutaraldehyde and Karnovsky. FTIR results showed that ultralene and paraffin undergo a dose‐dependent degradation of their vibrational profiles, consistent with radiation‐induced oxidative damage. In addition, formalin fixative has been shown to improve the preservation of the secondary structure of proteins in tissues compared with both glutaraldehyde and Karnovsky fixation. However, conclusive considerations cannot be drawn on the optimal fixation protocol because of the interference introduced by both substrate and embedding medium in the spectral regions specific to tissue lipids, nucleic acids and carbohydrates. Notably, despite the detected alterations affecting the chemical architecture of the sample as a whole, composed of tissue, substrate and embedding medium, the structural morphology of the tissues at the micrometre scale is essentially preserved even at the highest exposure dose.